Insulin Production and Resistance in Different Models of Diet-Induced Obesity and Metabolic Syndrome - Alwahsh, Salamah M. (Int J Mol Sci, 2017)
The role of the liver and the endocrine pancreas in development of hyperinsulinemia in different types of obesity remains unclear. Sedentary rats (160 g) were fed a low-fat-diet (LFD, chow 13% kcal fat), high-fat-diet (HFD, 35% fat), or HFD+ 30% ethanol+ 30% fructose (HF-EFr, 22% fat). Overnight-fasted rats were culled after one, four or eight weeks. Pancreatic and hepatic mRNAs were isolated for subsequent RT-PCR analysis. After eight weeks, body weights increased three-fold in the LFD group, 2.8-fold in the HFD group, and 2.4-fold in the HF-EFr (p < 0.01). HF-EFr-fed rats had the greatest liver weights and consumed less food during Weeks 4–8 (p < 0.05). Hepatic-triglyceride content increased progressively in all groups. At Week 8, HOMA-IR values, fasting serum glucose, C-peptide, and triglycerides levels were significantly increased in LFD-fed rats compared to that at earlier time points. The greatest plasma levels of glucose, triglycerides and leptin were observed in the HF-EFr at Week 8. Gene expression of pancreatic-insulin was significantly greater in the HFD and HF-EFr groups versus the LFD. Nevertheless, insulin: C-peptide ratios and HOMA-IR values were substantially higher in HF-EFr. Hepatic gene-expression of insulin-receptor-substrate-1/2 was downregulated in the HF-EFr. The expression of phospho-ERK-1/2 and inflammatory-mediators were greatest in the HF-EFr-fed rats. Chronic intake of both LFD and HFD induced obesity, MetS, and intrahepatic-fat accumulation. The hyperinsulinemia is the strongest in rats with the lowest body weights, but having the highest liver weights. This accompanies the strongest increase of pancreatic insulin production and the maximal decrease of hepatic insulin signaling, which is possibly secondary to hepatic fat deposition, inflammation and other factors.